Efeitos da divulgação de rankings e indicadores nas práticas contábeis dos municípios - Camargos Júnior, Paulo Guido de Novaes (2023)
Rankings and indicators have become increasingly widespread, both as a management tool for organizations and as external representations of their quality, efficiency, and responsibility to the public. The expansion use of rankings and indicators has been driven by technological advances, which offer the necessary resources to generate and capture information in this format. In the public sector, performance measurement has contributed to achieving some objectives, such as transparency of results and improvement in the provision of services to the population. The research aimed to verify how the accounting practices by local governments are affected by the disclosure of rankings and indicators prepared by external stakeholders. This dissertation, developed into two stages, a quantitative stage, and a qualitative stage. In the quantitative stage, the Ranking of Quality of Accounting Information in Siconfi, developed by the National Treasury Secretariat, was selected. Four hypotheses, derived from the literature, were defined to analyze this ranking. In the second stage, a qualitative and interpretative research was carried out, using semi-structured interviews as the main source of data collection and institutional legitimacy as a theoretical lens. 24 interviews were carried out with public managers, accountants, controllers, and consultants involved in the process of analysis or elaboration of rankings or indicators. As a result, the research demonstrated a learning effect in the quantitative stage, in which the municipalities have noticed the existence of rankings and acted to improve the selected indicators, in addition to identifying structure relationships with the improvement of the evaluated metrics and that deadlines defined by norms have had no effect on the priorities for action by municipalities. In the second stage, the effects of legitimacy through the dissemination of rankings and indicators, the flow of creation towards the beginning of internal changes, the strategies for improving practices and the conditions for changing internal practices were discussed. The results indicate that there are factors beyond the legitimacy of the ranking to produce improvements in practices by municipalities. The research contributes to helping ranking makers with a focus on defining metrics that better illustrate the reality of those ranked and thus generate a perception of stakeholders of the relevance of the defined metrics. And a contribution to the literature and the academic field, considering the scarcity of international and national works in the evaluation of the effects generated by rankings, considering public sector as an area of analysis. The results have implications for ranking and indicator developers, who must pay attention to the effects caused by the disclosure and definition of the metrics used, the effect of ceremonial adoption and manipulations that took place.